Emotional Suppression and its relationship to variables among middle school students - Salman, Muhammad Mazloum; Al-Ani, Intisar Kamal (Al-Adab Journal, 2021)
The current research aims to identify the emotional suppression among the students of the first (and third) grade students, and the significance of the difference in the emotional suppression according to the variable type (male and female) and the variable of academic achievement for the father. Stratified random from directorates (Rusafa and Karkh), the researcher has built a scale to measure emotional suppression, and after statistical treatment and data analysis, the researcher reached results stating that the research sample (first and third grade) has an emotional suppression, and there is no difference in the emotional suppression according to the type variable (Male and female), and there is no escape S in the emotional repression according to the achievement of the father and the mother, and in light of the results the researcher reached a number of recommendations and proposals, including: The work of advisory and preventive programs on how to reduce emotional repression and develop skillful thinking skills among students by activating the role of educational counselor in this aspect, especially in secondary schools, and conducting similar studies for the current research on other social segments and older age groups.